Les représentations sociales des fournisseuses de gamètes en Espagne : derrière le « don » d’ovocyte, un travail invisibilisé et dévalorisé ? - María Isabel Jociles; Ana María Rivas; Ariadna Ayala Rubio (Enfances, Familles, Générations, 2021)
Research Framework: Spain ranks first in Europe in the egg “donation” sector. The production and marketing of human oocytes constitute one of the most lucrative markets in the country. Objectives: How do women who offer their eggs understand this donation? In a society where egg “donation” is formally recognized as a voluntary and altruistic act, how do “donors” perceive and consider the remuneration they receive for this practice? Methodology: In-depth interviews were conducted with 38 egg donors from different regions of Spain, including current and past donors, aged between 18 and 49 years. Most interviewees held precarious jobs, were unemployed, and/or were students without scholarships. Results: Egg “donors” did not view their contribution to the human reproductive industry as work, let alone as waged work. Conclusions: Although these women play an essential role in the egg donation process, they are often undervalued. Yet their participation is necessary for the achievement of the family projects of intentional parents. They also contribute to the proper functioning of assisted reproduction clinics and to supplying gamete banks. Contribution: By presenting the social organization of egg donation in Spain, this article sheds light on how the reproductive work carried out by women that produce and give up their eggs is rendered invisible and undervalued. In addition, it gives an account of how biological material is expropriated from egg “donors” – an expropriation that is inadequately compensated and from which they do not benefit. This exploitation of women through the “biomedical mode of reproduction” and the invisibilization of their work is made possible thanks to “donor” anonymity, phenotypic coordination, modes of consent, economic compensation, and, more broadly, the use of the “gift” metaphor and the ideology of altruism.